2016
DOI: 10.1099/ijsem.0.001148
|View full text |Cite
|
Sign up to set email alerts
|

Bradyrhizobium stylosanthis sp. nov., comprising nitrogen-fixing symbionts isolated from nodules of the tropical forage legume Stylosanthes spp.

Abstract: Bradyrhizobium stylosanthis sp. nov., comprising nitrogen-fixing symbionts isolated from nodules of the tropical forage legume Stylosanthes spp. The introduction of legumes and nitrogen-fixing bacteria in tropical areas under pasture is a key factor for improvement of soil fertility. However, there are still very few studies concerning the symbionts of tropical forage legumes. We performed a polyphasic study with three strains representing the genus Bradyrhizobium (BR 446 T , BR 510 and BR 511) isolated from t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 39 publications
(9 citation statements)
references
References 39 publications
0
9
0
Order By: Relevance
“…The 16S rRNA gene phylogeny () split the Bradyrhizobium type strains into the two well-known superclades of Bradyrhizobium japonicum (GI) and Bradyrhizobium elkanii (GII) [2, 8–10, 33]. All strains from our study were clustered in the B.…”
Section: Phylogenymentioning
confidence: 99%
See 1 more Smart Citation
“…The 16S rRNA gene phylogeny () split the Bradyrhizobium type strains into the two well-known superclades of Bradyrhizobium japonicum (GI) and Bradyrhizobium elkanii (GII) [2, 8–10, 33]. All strains from our study were clustered in the B.…”
Section: Phylogenymentioning
confidence: 99%
“… Bradyrhizobium is considered as the probable ancestor lineage of all rhizobia and, in the last decade, several studies reported remarkable genetic diversity within the genus, as well as symbiotic associations with an increasing number of legumes [e.g. [1, 2, 6–13]. The environmental and economic applications of Bradyrhizobium and its high diversity reassure the importance of characterization and seeking for strains with biotechnological potential.…”
Section: Full-textmentioning
confidence: 99%
“…( Supplementary data Table S1 ). The majority of Clade VII strains originate from North and South America, while some were isolated in south-east Asia (southern China, the Island of Okinawa, Thailand, and the Philippines) [ 143 , 144 , 145 , 146 , 147 ]. Given that Clade VII bradyrhizobia from south-east Asia occupy internal positions relative to the American strains, it can be assumed that this cluster has evolved in the Americas, possibly, in an area of hot and humid tropical climate.…”
Section: Phylogeny Of Symbiotic Loci Of Genisteae-nodulating mentioning
confidence: 99%
“…The ANI approach has recently been accepted as an alternative to the traditional DNA: DNA hybridization method (Delamuta et al 2016;Baraúna et al 2016) and similarity values >95-96% are considered as the threshold to determine if two bacterial strains belong to the same species (Richter and Rosselló-Mora 2009).…”
Section: Ani and Dna G + C Contentmentioning
confidence: 99%